Daya Tarik Kebudayaan Batak terhadap Tingkat Kunjungan Wisatawan di Kabupaten Samosir - Irik Maida Simbolon; Merry Moy Mita (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
This research aims to analyze the influence of the attractiveness of Batak culture on the level of tourist visits in Samosir Regency. This research data is in the form of primary and secondary data. The sampling process in this research used purposive sampling with a sample size of 80. Data analysis techniques used descriptive analysis and multiple linear regression tests. It can be concluded that the attractiveness of Batak culture influences the level of tourist visits in Samosir Regency. This can be seen from the value of the Simultaneous Test (T Test) which is used to determine the percentage influence of the independent variable (X) on the dependent variable (Y). The results obtained show that the Fcount value is 6.681. Meanwhile, Ftable is 2.495, so Fcount is greater than Ftable (6.681> 2.495) or a significant level of 0.000 or sig F <5% (0.000<0.05). This means that together the Attraction variable influences the level of visits (Y) of cultural tourism in Samosir Regency. So in this case, cultural tourism destinations have the potential to be developed into tourist attractions so that they can increase the level of local and foreign tourist visits.